A new story in the structural chemistry of cerium(IV) phosphate - Nazaraly, Micaela; Chanéac, Corinne; Ribot, François; Wallez, Gilles; Quarton, Michel; Jolivet, Jean-Pierre (The Journal of physics and chemistry of solids, 2007)
Two different cerium(IV) phosphates have been prepared by ageing at 95 °C an aqueous solution made from Ce(NO 3) 6(NH 4) 2, nitric acid, and phosphoric acid with the following conditions: P/Ce=2, [HNO 3]=5.8 M and [Ce 4+]=0.1 M. The control over the formed solid was achieved through the ageing time. After 18 h, a metastable compound ( A), corresponding to Ce(PO 4) 1.5(H 2O)(H 3O) 0.5(H 2O) 0.5, is obtained, while after 5 days a stable one ( B), corresponding to Ce(PO 4)(HPO 4) 0.5(H 2O) 0.5, is recovered. Both solids exhibit a P/Ce ratio of 1.5. Their structures, 31P solid state NMR, and thermal behaviors are compared.